Transmigration In Jambi Province From The Perspective of Regional Policymakers - Junaidi Junaidi (Jambura Agribusiness Journal, 2022)
This study aims to analyze the current state of ex-transmigration villages and regional policy makers' perceptions regarding transmigration's existence and sustainability. The study was conducted in Jambi Province. This research uses a descriptive qualitative approach. Primary data collection was carried out through Focus Group Discussions (FGD) with policymakers at the provincial and district levels. According to the study’s results, the implementation of the transmigration program in addition to showing various successes also resulted in a number of negative excesses for the destination areas. These negative excesses are mainly related to the disparity between the transmigration area and its surrounding area, the low leverage of the transmigration area on the surrounding area, and the potential emergence of poverty in the transmigration area. Related to this, future revitalization of the transmigration program must focus on the development of transmigration areas that are functionally related to the surrounding area, based on the expertise required by the local area, and increasing the role of the community and private sector in the diversification transmigrant business patterns.